2016
DOI: 10.1111/exd.13162
|View full text |Cite
|
Sign up to set email alerts
|

Microbial elements as the initial triggers in the pathogenesis of polymorphic light eruption?

Abstract: The primary trigger of polymorphic light eruption (PLE) remains to be uncovered. We hypothesize that PLE may be initiated by elements resulting from UV‐induced damage to microbial communities of the skin, leading to a cascade of events eventually resulting in the skin rash of the disease. One mechanism by which epidermal injury by UV radiation could trigger PLE are danger signals such as damage or pathogen associated molecular patterns DAMP/PAMPs or commensal‐associated molecular patterns (CAMPs). Such trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
(11 reference statements)
1
29
0
Order By: Relevance
“…In PLE, IL‐1β levels have been found to be elevated, and this could induce high psoriasin expression in the skin. Psoriasin displays a strong, selective antimicrobial activity against Escherichia coli strains, and this could theoretically hint toward the involvement of E. coli or its components in PLE lesions which is yet to be investigated …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PLE, IL‐1β levels have been found to be elevated, and this could induce high psoriasin expression in the skin. Psoriasin displays a strong, selective antimicrobial activity against Escherichia coli strains, and this could theoretically hint toward the involvement of E. coli or its components in PLE lesions which is yet to be investigated …”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs during spring or early summer upon exposure to sunlight and the symptoms usually subside with repeated sunlight exposure due to continuous natural photo hardening as the summer progresses or after medical photo hardening . The exact etiology and pathogenesis of PLE still remain a mystery; however, resistance to UV‐induced immunosuppression and type IV delayed‐type hypersensitivity (DTH) to photo‐antigens are believed to play a key role in the disease . The physiological occurrence of UV‐induced immunosuppression may protect healthy subjects from symptoms of PLE by suppressing the immune reaction to newly formed (photo) antigens probably due to regulatory T cells, whereas in PLE prone subjects, a failure of immune suppression might favor the occurrence of the skin rash of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have also suggested that innate antimicrobial peptides (AMP) may be involved in pathogenesis of PLE . Normally, UVR‐induced AMP contributes to immunosuppression inducing Tregs, otherwise in early stages of PLE a dysregulated AMP expression following UVR could play some part in the failure of photoimmunosuppression .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Patra and Wolf contribute a Hypothesis Letter on the possible involvement of the skin's microbiome in polymorphic light eruption, while Wolf et al . examine in a viewpoint on psoriasis management by phototherapy why the latter is not always beneficial and can aggravate the condition in photosensitive patients.…”
mentioning
confidence: 99%